Sur quelles bases enseigner l'intercompréhension entre les langues slaves de l'ouest et du sud-ouest ? - Labbé, Grégoire (Vestnik za tuje jezike, 2017)
Intercomprehension between similar languages of the same family is to a certain measure a natural phenomenon. However, comprehension of a close language will very often be disturbed by many opaque elements, which are not understandable without a better knowledge of its grammar or vocabulary. A methodology similar to the one offered by the manual Eurom 5 allows learners to work on their comprehension of a language family and its functioning. In Eurom 5, the learning process is focused on the knowledge of a "romance system", bringing out the particularities of each of the languages dealt with within the manual. With such a system in place, a better comprehension of these languages is guaranteed. We have been trying to adapt such a concept to western
Keywords: medjezikovno razumevanje; intercomprehension; Romance languages; romanski jeziki; Slavic languages; slovanski jeziki; Slovene; Slovenian; slovenščina; Czech; češčina; Croatian; hrvaščina; didaktika jezika; languages didactics